The crisis in context democratic capitalism and its contradictions - Wolfgang Streeck (Max Planck Institute for the Study of Societies, 2011)
The 'financial crisis' and its sequel, the current sovereign debt crisis, appear to be the latest permutations of an old conflict between capitalism and democracy that forcefully reasserted itself after the end of the postwar growth period. Today's calamities were preceded by high inflation in the late 1960s and 1970s, rising public deficits in the 1980s, and growing private indebtedness in the 1990s and 2000s. In each case, governments were faced with popular demands for prosperity and security that were incompatible with market allocation. Inflation, deficits and financial under-regulation should not be understood as results of faulty economic management but rather as temporary stopgaps to simultaneously satisfy democratic-political claims for social justice and economic claims for profitability. As the site of distributional conflict moved with time from the labor market and industrial relations to the politics of public spending, then to the provision of credit to private households, and from there to international fiscal diplomacy, it became increasingly insulated against popular democratic pressures. At the same time, the political and economic risks associated with the contradictions of democratic capitalism have increased, with potentially disruptive consequences for the social integration of democratic polities as well as for the system integration of advanced market economies. – – Die sogenannte Finanzkrise von 2008 und die anschließende Krise der Staatsfinanzen müssen als jüngste Manifestation eines alten Konflikts zwischen Kapitalismus und Demokratie gesehen werden, der mit dem Ende der Wachstumsperiode der Nachkriegszeit neu aufgelebt ist. Vorläufer der heutigen politisch-ökonomischen Verwerfungen waren die Inflation der späten 1960er und der 1970er Jahre, die steigenden Haushaltsdefizite der 1980er Jahre und die zunehmende Privatverschuldung seit Mitte der 1990er Jahre. In allen Fällen waren demokratische Regierungen mit Forderungen nach steigenden Einkommen und sozialer Sicherheit konfrontiert, die mit einer Allokation von Ressourcen nach den Spielregeln freier Märkte unvereinbar waren. Inflation, Haushaltsdefizite und Unter-Regulierung der Finanzmärkte waren im Kern nicht Folgen fehlerhafter Wirtschaftspolitik, sondern dienten der zeitweiligen Zufriedenstellung demokratisch-politischer Forderungen nach sozialer Gerechtigkeit, die mit wirtschaftlichen Forderungen nach Profitabilität und Verteilung nach Maßgabe marginaler Produktivität unvereinbar waren. In dem Maße, wie die Auseinandersetzung sich vom Arbeitsmarkt und den Arbeitsbeziehungen auf die öffentliche Haushaltspolitik, anschließend auf die Politik der Regulierung des Finanzsektors und von da auf die internationale Geldpolitik verlagerte, wurde der demokratisch-kapitalistische Verteilungskonflikt zunehmend gegen demokratischen Druck von unten isoliert. Gleichzeitig nahmen die den Widersprüchen des demokratischen Kapitalismus inhärenten Risiken zu, mit potenziell schwerwiegenden Folgen sowohl für die soziale Integration demokratischer Gesellschaften als auch die Systemintegration fortgeschrittener Marktwirtschaften.
Keywords: 300